2020
DOI: 10.1038/s41375-020-0990-y
|View full text |Cite
|
Sign up to set email alerts
|

Advances in understanding of angioimmunoblastic T-cell lymphoma

Abstract: It has been nearly half a century since angioimmunoblastic T-cell lymphoma (AITL) was characterized in the early 1970’s. Our understanding of the disease has dramatically changed due to multiple discoveries and insights. One of the key features of AITL is aberrant immune activity. Although AITL is now understood to be a neoplastic disease, pathologists appreciated that it was an inflammatory condition. The more we understand AITL at cellular and genetic levels, the more we view it as both a neoplastic and an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
128
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(132 citation statements)
references
References 121 publications
2
128
0
2
Order By: Relevance
“…Interestingly, hypergammaglobulinemia was shown more in AITL, less in other TFH lymphomas [ 8 ]. In histopathologic findings, AITL is characterized by the proliferation of high endothelial venules and mixed inflammatory cell infiltration, which is not prominent in other TFH lymphomas [ 35 , 36 ]. Hypergammaglobulinemia is caused by increased immunoglobulin production of polyclonal plasma cells, and this phenomenon can be considered a result of specific immunogenic stimulation of AITL.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, hypergammaglobulinemia was shown more in AITL, less in other TFH lymphomas [ 8 ]. In histopathologic findings, AITL is characterized by the proliferation of high endothelial venules and mixed inflammatory cell infiltration, which is not prominent in other TFH lymphomas [ 35 , 36 ]. Hypergammaglobulinemia is caused by increased immunoglobulin production of polyclonal plasma cells, and this phenomenon can be considered a result of specific immunogenic stimulation of AITL.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in extranodal NK/T-cell lymphomas, the virus, detected in 71% of cases, infects tumor cells where it is constantly detected. Angioimmunoblastic T cell lymphoma (AITL), which is the focus of our work, is probably the most common form of PTCL [19] although less common in North America or Asia than in Europe, accounting respectively for 16-34.4%, 17.9-22.4%, and 28-34% of PTCLs [20,21]. AITL, which mostly affects elderly people [22], is clinically characterized by generalized lymphadenopathy often accompanied by hepatosplenomegaly, skin rash, and B-cell modifications associated with immunologic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…10,16 Furthermore, immunohistochemical studies using four commercially available stains for GATA3, CXCR-4, T BX 21 and CXCR 3 in unformatted fixed paraffin embedded tissue can help classified the and the other type having depleted follicles. 21 The primary presentation of these two subtypes is nodal with a plethora of associated symptoms including arthralgias and skin rashes -autoimmune phenomena that can be explained by the role of T FH cells in the regulation of B cells. However, non-nodal presentations can occur especially in relapsed disease.…”
Section: Peripheral T-cell Lymphoma Not Other Specifiedmentioning
confidence: 99%
“…Downstream effects include inhibition of the TET2 family of Gene expression profiling of 114 cases of AITL has shown that potent angiogenic and pro inflammatory cytokines are expressed, including IL-8, IL6, IL18, IL-10 and IL21. The IDH2 mutations are also linked to increased blood vessel formation 21. This dysregulated function of the TFH induces a set of cytokines that result in the inflammatory components of AITL 23.…”
mentioning
confidence: 99%